ANALISIS KEMAMPUAN PENALARAN MATEMATIKA SISWA PADA MATERI HIMPUNAN - Fungky Marian (Hipotenusa Journal of Research Mathematics Education (HJRME), 2021)
Reasoning is a process of thinking to get a conclusion from an idea or ideas that can be justified. The purpose of this study was to determine how students' mathematical reasoning abilities in the set material. The method in this research is descriptive quantitative to describe and analyze how high the level of students' mathematical reasoning. The subjects of this study were students of class VII A SMP Negeri 2 Berbah. Based on the results of the study, it was found that the level of students' mathematical reasoning was still in the sufficient category, so it is necessary for a learning method that can stimulate students so that mathematical reasoning becomes better.